Pathological Mobilization and Activities of Dendritic Cells in Tumor-Bearing Hosts: Challenges and Opportunities for Immunotherapy of Cancer - Tesone, Amelia J.; Svoronos, Nikolaos; Allegrezza, Michael J.; Conejo-Garcia, Jose (Frontiers in Immunology, 2013)
A common characteristic of solid tumors is the pathological recruitment of immunosuppressive myeloid cells, which in certain tumors includes dendritic cells (DCs). DCs are of particular interest in the field of cancer immunotherapy because they induce potent and highly specific anti-tumor immune responses, particularly in the early phase of tumorigenesis. However, as tumors progress, these cells can be transformed into regulatory cells that contribute to an immunosuppressive microenvironment favoring tumor growth. Therefore, controlling DC phenotype has the potential to elicit effective anti-tumor responses while simultaneously weakening the tumor’s ability to protect itself from immune attack. This review focuses on the dual nature of DCs in the tumor microenvironment, the regulation of DC phenotype, and the prospect of modifying DCs in situ as a novel immunotherapeutic approach.